2023
DOI: 10.3389/fnins.2023.1110942
|View full text |Cite
|
Sign up to set email alerts
|

Methylmalonic acidemia: Neurodevelopment and neuroimaging

Abstract: Methylmalonic acidemia (MMA) is a genetic disease of abnormal organic acid metabolism, which is one of the important factors affecting the survival rate and quality of life of newborns or infants. Early detection and diagnosis are particularly important. The diagnosis of MMA mainly depends on clinical symptoms, newborn screening, biochemical detection, gene sequencing and neuroimaging diagnosis. The accumulation of methylmalonic acid and other metabolites in the body of patients causes brain tissue damage, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Examples of genes for which we found converging evidence in neuroticism for transcript and protein level associations with neuroticism include low density lipoprotein receptor-related protein 4 ( LRP4), syntaxin 4 ( STX4 ), and metabolism of cobalamin associated B ( MMAB ) (Supplementary Sheet 8). LRP4 has diverse roles in neuromuscular junction and in disorders of the nervous system including Alzheimer’s disease and amyotrophic lateral sclerosis [46], STX4 is implicated in synaptic growth and plasticity [47], and MMAB , which catalyzes the final step in the conversion of cobalamin (Vitamin B12) into adenosylcobalamin (biologically active coenzyme B12), all of which have broad implications for brain function including those in relation to methylmalonic acidemia [48]. Low levels of plasma vitamin B12 have been found to be associated with higher depression cases in multiple studies [49].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of genes for which we found converging evidence in neuroticism for transcript and protein level associations with neuroticism include low density lipoprotein receptor-related protein 4 ( LRP4), syntaxin 4 ( STX4 ), and metabolism of cobalamin associated B ( MMAB ) (Supplementary Sheet 8). LRP4 has diverse roles in neuromuscular junction and in disorders of the nervous system including Alzheimer’s disease and amyotrophic lateral sclerosis [46], STX4 is implicated in synaptic growth and plasticity [47], and MMAB , which catalyzes the final step in the conversion of cobalamin (Vitamin B12) into adenosylcobalamin (biologically active coenzyme B12), all of which have broad implications for brain function including those in relation to methylmalonic acidemia [48]. Low levels of plasma vitamin B12 have been found to be associated with higher depression cases in multiple studies [49].…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse white matter swelling, severe leukoaraiosis of varying degrees, hydrocephalus, corpus callosum atrophy, and symmetric bilateral lesions of the basal ganglia are frequent and distinctive imaging findings in early-onset cblC disease. However, late-onset cases often exhibit cerebral atrophy and patchy lesions in the deep white matter (17)(18)(19). Cerebellar involvement is uncommon in cblC disease, and literature review reveals only seven reported cases with cerebellar symptoms or imaging changes (12,16,18,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…93 The outcome is guarded. 94 However, many cases with cobalamin-responsive subtypes may have better prognosis. 9,85 1C.…”
Section: Future Studiesmentioning
confidence: 99%